Examining factors affecting the adoption and usage of document workflow management system (DWMS) using the UTAUT model: Case of Botswana. (21st March 2016) - Mosweu, Olefhile; Bwalya, Kelvin; Mutshewa, Athulang
Abstract : Purpose: – Public sector organisations in the developing world contexts have hugely invested in procuring information management systems such as the electronic document and records management system (EDRMS). The procurement and implementation of these systems come at a huge cost to taxpayers. Unfortunately, most of these systems remain white elephants due to reluctance by the anticipated users to adopt and use them in their information management endeavours. This study aims to understand Action Officers' perceptions of, adoption and/or usage of the document workflow management system (DWMS) at the Ministry of Trade and Industry in Botswana. The DWMS is one type of EDRMS. Design/methodology/approach: – The survey uses a questionnaire distributed in Gaborone, Botswana to gather data on the perceptions of anticipated users of the DWMS. The study used a modified form of UTAUT as a theoretical lens to explore user's perception on the adoption and use of DWMS at the Ministry of Trade and Industry, Botswana. The population of the study was 68. A total of 53 (86.89 per cent) out of 61 users of DWMS were purposively sampled and responded to the questionnaire. The rest took part in interviews. Findings: – Negative attitudes to computers, computer anxiety, the complexity of DWMS and its incompatibility to current working practices influences Action and Records Officers' unwillingness to adopt and use the DWMS. Research limitations/implications: – This study was limited to the Ministry of Trade and Industry (MTI)'s Department of Corporate Services, so its findings cannot be statistically generalized to the MTI as a whole. Another limitation relates to the secretive nature of staff in some government departments which lead them to provide partial information related to the study. Finally, the additional technology adoption factors discovered from interviews (i.e. computer anxiety, incompatibility of DWMS to current work practices, negative attitudes to system use and complexity of the system) have not been empirically tested to ascertain their validity. This provides an opportunity for a future study to empirically test the said additional factors. Practical implications: – To mitigate the lower DWMS adoption and usage, robust change management and communication were identified as some of the critical factors that should be considered. The identified factors may be used in drafting a model to aid the implementation of DWMS in Botswana or in a contextually similar environment in the developing world. Originality/value: – This study provides empirical evidence from an original study.